NUMERICAL INVESTIGATION OF HEAT TRANSFER AND FLOW CHARACTERISTICS IN SHELL-AND U-TUBE HEAT EXCHANGER WITH BAFFLES - FAHAD, SADOUN; ALSHARA, AHMED KADHIM; SAEED, MURTATHA (Journal of Duhok University, 2017)
In this paper the numerical model of cylindrical coordinates, three dimensional of a laminar heat transfer and fluid flow inside shell and tube heat exchanger is examined. The thermo-hydraulic performance of heat exchangers is predicted with finite volume method by CFD simulations using ANSYS 15.0 code. Shell-and-tube heat exchanger is consisted of one pass of warm water laminar flow at the shell side and two passes single tube of laminar cold water. The annular baffles are inserted on shell side, and on the facing distances of the length of tube from the outer surface. Baffles are inserted with staggered position on the shell and tube to achieve good fluid circulation. Also baffles on the tube side are varied with angle inclination, number and diameter while only number and length on the shell side. The tube baffles angle inclination as (45º, 0º and -45 º) and without baffles and the range of Reynolds number from 100 to 2000. The results show high effect of baffles angles on the heat exchanger performance at high Reynolds number. Maximum heat transfer from hot fluid occurs at baffle with angle 0o and high 30mm. Also baffles number increases Nusselt number at high fluid flow rate while a little effect of baffle height and number on the fluid pressure drop is absorbed as obtained by Mica et.al [1].